The ethnobotany of Christ's Thorn Jujube (Ziziphus spina-christi) in Israel - Levy Shay; Dafni Amots; Lev Efraim (BMC, 2005)
Abstract This article surveys the ethnobotany of Ziziphus spina-christi (L.) Desf. in the Middle East from various aspects: historical, religious, philological, literary, linguistic, as well as pharmacological, among Muslims, Jews, and Christians. It is suggested that this is the only tree species considered "holy" by Muslims (all the individuals of the species are sanctified by religion) in addition to its status as "sacred tree " (particular trees which are venerated due to historical or magical events related to them, regardless of their botanical identity) in the Middle East. It has also a special status as "blessed tree" among the Druze.